Perbandingan Efektiï¬tas Penyikatan Gigi dengan Bulu Sikat Soft dan Hard Termasuk Indeks Plak - Priutami, Lyza; Dewi, Anne Handrini (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2008)
The hardness of the toothbrush bristle is the important factor to be paid attention because it is directly felt when brush the teeth and related to the effect of tooth cleaning. The aim of this research is to get more information about effectiveness between soft and hard toothbrush bristle in clean up the plaques.This research is experimental with 30subjects girl of University Muhammadiyah collage which is divided in to two groups (soft and hard group). Every group has 15 subjects and include on criteria which has been determined during I week. The researcher did examination of subjects plaques before and after brushing their teeth with toothbrush that gave by researcher: Subject asked to toothbrush 2 times a day with bass method in 2 minutes. The result was analyzed with independent t-test sample.The result showed that there was signiï¬cant difference between soft bristle and hard bristle in before and after brushing (p 0, 05). On this result hard bristle shows more difference assess than soft bristle. In conclusion, hard bristle more effective than soft bristle in remove the plaque.